2016
DOI: 10.1016/j.physbeh.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Posture effects on spontaneous limb movements, alternated stepping, and the leg extension response in neonatal rats

Abstract: The development of postural control is considered an important factor for the expression of coordinated behavior such as locomotion. In the natural setting of the nest, newborn rat pups adapt their posture to perform behaviors of ecological relevance such as those related to suckling. The current study explores the role of posture in the expression of three behaviors in the newborn rat: spontaneous limb activity, locomotor-like stepping behavior, and the leg extension response (LER). One-day-old rat pups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
(129 reference statements)
1
3
0
Order By: Relevance
“…Although we subjected mice to different postures (prone and supine), the behavioral activity patterns remained. We found minor differences in the number of spontaneous limb movements in a supine rather than the prone posture, similar to Mendez and colleagues 37 .…”
Section: Discussionsupporting
confidence: 91%
“…Although we subjected mice to different postures (prone and supine), the behavioral activity patterns remained. We found minor differences in the number of spontaneous limb movements in a supine rather than the prone posture, similar to Mendez and colleagues 37 .…”
Section: Discussionsupporting
confidence: 91%
“…In rats, a series of studies demonstrated how neonates adapt their locomotor behavior to environmental context ( Figures 1A,B ). For example, Mendez-Gallardo et al ( 2016 ) explored the role of posture in the expression of spontaneous limb movements and showed that rat pups expressed more spontaneous activity while supine than prone ( Figure 1A ). Contrarily, more stepping was observed in the prone position, suggesting that posture affects the expression of different behaviors during early development.…”
Section: Early Modulation Of Locomotor Precursorsmentioning
confidence: 99%
“…Also, knee extensor (FT) and ankle extensor (LG) activity dropped out (adapted from Bradley et al, 2014 ). Right: a greater number of SMs of newborn rat pups in supine than in prone position (from Mendez-Gallardo et al, 2016 ). (B) A smaller number of alternated forelimbs steps induced by drug treatment (quipazine) on a stiff substrate as compared to an elastic or no substrate (adapted from Brumley et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the spinal in vivo neonatal rat preparation is more directly relevant to SCI, the intact neonatal rat offers important insights into general issues of neurobehavioral development and plasticity as well. For example, it has been shown that locomotor behavior in intact newborn rats is modulated by the substrate that the animal is stepping on [188], ROM restriction [191], treadmill speed [215], posture [216], and testing environment [187]. Thus even before the onset of independent walking and maturation of neural pathways (e.g., corticospinal tract development, myelination), it is clear that locomotor mechanisms demonstrate plasticity and are responsive to the environment.…”
Section: Synergistic Effects Of Pharmacological and Sensory Stimulatimentioning
confidence: 99%